The Analysis of Learning Outcome Assessment from an Islamic Psychopedagogical Perspective and Its Implementation in Contemporary Education - Saputri, Sherli Dwi Andri; Batubara , Juliana; Deliani , Nurfarida (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This article examines the concept of learning assessment from the perspective of Islamic psychopedagogy and its relevance to contemporary education. Using a qualitative library research method, this study analyzes theories from educational experts and Quranic foundations related to assessment principles, including validity, reliability, objectivity, practicality, and usability. The results show that learning assessment functions not only as a measurement tool for cognitive achievement but also as a means of fostering affective and psychomotor development. Islamic principles emphasize fairness, proportionality, accountability, and appreciation for effort, which align with modern assessment approaches such as authentic assessment and competency-based evaluation. Current issues including imbalance between formative and summative assessment, the challenge of assessing character, and the integration of digital technology are also discussed. This study concludes that holistic assessment-integrating pedagogical theory and Islamic values—is essential to developing an equitable and meaningful learning process.